Methotrexate and immunogenicity of vaccines in patients with rheumatic diseases - В. S. Belov; N. V. Muravyeva; Е. L. Nasonov (Научно-практическая ревматология, 2024)
Currently, methotrexate (MT) remains one of the immunosuppressive drugs most commonly used in rheumatology. However, its effect on the immunogenicity of vaccines has until recently been studied only to a limited extent, which has led to the lack of clear recommendations for the use of MT during vaccination. Significant progress was made during the COVID-19 pandemic due to the dynamic development of vaccine research, including in patients with immuno-inflammatory rheumatic diseases. The review presents data on the effect of MT on the immunogenicity of vaccines against influenza, pneumococcus, herpes zoster, tetanus/diphtheria/pertussis, yellow fever and COVID-19 (including humoral and cellular responses) in rheumatological patients. The necessity of observing certain time intervals during vaccination in the case of MT use has been demonstrated. The potential mechanisms by which MT influences the immunogenicity of vaccines are presented. The importance of further clinical studies is emphasized in order to assess the effect of MT therapy on the vaccine response and to develop methods for its optimization.